EFEKTIVITAS BRIKET KULIT PINANG TERHADAP PENURUNAN NILAI KADAR AIR DAN NILAI DENSITAS - Rani Saputri; Jumiati, Ety; Sirait, Ratni (ELEMEN : JURNAL TEKNIK MESIN, 2023)
Utilization of briquettes as an alternative biomass energy source is possible. Biomass is a renewable energy source that is becoming increasingly important throughout the world. This has the potential to reduce human dependence on fossil fuels. This research aims to determine the effectiveness of reducing the water content and density values of areca nut shell briquettes. The raw materials used in making briquettes are areca nut shells and arpus adhesive, with each percentage of material and adhesive composition, namely sample A (55% : 45%), sample B (60% : 40%), sample C (65% : 35%), and sample D (70% : 30%). The results of this research obtained a water content value of 6.36% - 4.82% and a density value of 0.534 g/cm3 - 0.599 g/cm3. This water content value meets SNI 01-6235-2000 regarding wood charcoal and these briquettes are suitable to be used as a substitute for charcoal on a household scale.